Workplace safety and health assessing current practices and promoting change in the profession - Schneid, Thomas D. (CRC Press, Taylor and Francis, 2014)
"The safety profession often clings to the basic believes and practices which evolved during the early years after the announcement of the Occupational Safety and Health Act in 1970. This book reviews and challenges many of the commonly accepted practices as well as misconceptions about safety in the workplace and provide new and innovative options for safety professionals to consider. It examines many of the basic assumptions in the safety profession and challenge the reader to assess and evaluation their activities in search of a better and more effective way of achieving the results necessary to be competitive in today's workplace"-- Provided by publisher.
Keywords: Industrial safety.; elektronické knihy; electronic books